2015
DOI: 10.1002/bdm.1903
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analytic Investigations of the Relation Between Intuition and Analysis

Abstract: Over 50 years of research on cognitive style has converged on the importance of individual differences in use of intuition and analysis. This program of research is characterized, however, by two incompatible perspectives about the relation between intuition and analysis. The distinction concerns whether intuition and analysis are opposite poles of a single dimension or whether they are orthogonal constructs. Two studies report meta‐analytic investigations of the relation between intuition and analysis. A meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 113 publications
5
76
0
Order By: Relevance
“…Conversely, the rational urgent decision factor was positively associated with conscientiousness, and negatively associated with neuroticism, openness to experience, and extraversion. Finally, the differences in the associations between urgent decisions and the Big Five and between generalized decision making tendencies and the Big Five (Wang et al, 2015) support the notion that the construct urgent decision making under extreme circumstances and the construct generalized preference for decision making are different from each other. In this sense, these differences show that the hypothesized need for an instrument to measure urgent decisions is well-founded.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Conversely, the rational urgent decision factor was positively associated with conscientiousness, and negatively associated with neuroticism, openness to experience, and extraversion. Finally, the differences in the associations between urgent decisions and the Big Five and between generalized decision making tendencies and the Big Five (Wang et al, 2015) support the notion that the construct urgent decision making under extreme circumstances and the construct generalized preference for decision making are different from each other. In this sense, these differences show that the hypothesized need for an instrument to measure urgent decisions is well-founded.…”
Section: Discussionmentioning
confidence: 66%
“…Firstly, taking into account that the BUDECI assesses the affective and rational bases for urgent decision-making under extreme circumstances, the scores of the affective urgent decision factor and the scores of the rational urgent decision factor were positively associated with the scores of PID tendency to intuition and the scores of PID tendency to deliberation, respectively. Secondly, on the whole, the affective urgent decision and rational urgent decision factors were associated with the Big Five factors similarly to the way the Big Five factors were associated with the generalized disposition to intuition and to rationality (Wang et al, 2015). However, it is noteworthy that other associations were found between urgent decisions and the Big Five.…”
Section: Convergent and Discriminant Validitymentioning
confidence: 68%
See 1 more Smart Citation
“…Wang et al .’s () recent meta‐analysis reviewed evidence relating to the validity of the unitary vs. dual models. From a database of 80 studies ( N = 27,501) Wang et al .’s () analyses showed clearly that intuition and analysis are uncorrelated, thereby strongly supporting the dual model. Wang and colleagues () concluded that their findings are consistent with previous research supporting a dual view (e.g.…”
Section: Psychological and Psychometric Issues In The Relationship Bementioning
confidence: 99%
“…They propose that analytical and intuitive processes are independent dimensions that fulfill different functions, and recent studies support this conceptualization (Akinci and Sadler-Smith 2013;Hodgkinson et al 2009;Wang et al 2017). In their meta-analysis, Wang et al (2017) show the independence of the analysis and intuition constructs. These results are underpinned by Simon (1987, p. 61), who states:…”
Section: The Nature and Structure Of Cognitive Stylesmentioning
confidence: 91%